Optimizing The Utilization of Candi Banana as Functional Food and Import Substitution of Industrial Raw Materials through The Application of Appropriate Technology - Soesilowati, Etty; Mizar, M. Alfian; Fauzan, Slamet; Nusa, Cassandra Permata; Nurinda, Mei Sulfia (Universitas Muhammadiyah Surakarta, 2024)
Indonesia is one of the countries known as the world's banana (Musa Paradisiaca) producer, where 50% of Asian banana production comes from Indonesia. Bananas are one of the sources of prebiotics that fight free radicals that trigger oxidative stress, especially for people with hypercholesterolemia, Alzheimer's Disease, and Autism. There is a type of Pisang Candi (Musa Paradisiaca Fa. Corniculata) that is gluten free and is the largest commodity in Malang Regency, especially Sidodadi village. The research aims to process bananas into various forms of functional food through the use of appropriate technology and test their physiochemical content. The method of activity was carried out through technological engineering and proximate testing through a research & development approach. The results showed that 100 grams of banana flour contained 3.297% protein, 82.966% carbohydrate, 0.573% fat, 2.384% ash/mineral, and 10.780% water. For the banana to have a long shelf life and not easily experience browning due to its polyphenol content, it is dried and made into flour. The benefits of the research and development are increased capacity of farmers, increased quality and added value of temple banana products, and the availability of import substitution of industrial raw materials, which has implications for increasing their income.